Rancangan Robotik Marshaller dalam Pemanduan Parkir Pesawat sebagai Media Pembelajaran di Politeknik Penerbangan Makassar - Sabur, Fatmawati; Mantako, Elsaday (Politeknik Penerbangan Makassar, 2021)
The height movement of aircraft on movement area at some airport need a good coordination between operational officer ATC (Air Traffic Controller) and AMC (Aircraft Movement Control). Aircraft which has been passing taxi area will guided by marshaller to park on the appron based on the parking stand set by AMC, so the aircraft parking arranged well and suitable to the applicable regulation (2015 KP 39 Standard Technique and Operation PKSP Part 139 Volume I Aerodrome). A professional resource are needed to handle aircraft on the apron so the effectiveness and efficiency of the movement could be applied. The objective of this research was to produce in order that to Marshaller Robotic in control of aircraft parking as an education media give knowledge and skills for Marshalling trainer at CASEA of Makassar regarding aircraft parking on apron. This marshaller hardware design used control system in microcontroller (Arduino mega 2560) and data communication via Bluetooth with the aircraft, which the movements were based on Annex 2 (rule of the air) about Marshalling Signals. The result of this design gave an easier perspective to understand by trainer instead of giving lesson through white board or power point. Beside of that, this simulation perspective can be seen through all sides of the aircraft, marshaller and marka on the aerodrome at once. So, through this design CASEA of Makassar could increase quality of human resources of the marshalling trainer.